Efficient control of light propagation assisted by photothermal effect in a graphene-integrated all-fiber device - Ha, Seongju; Hun Park, Nam; Choi, Kyuhong; Jun Ahn, Kwang; Yeom, Dong Il (Optics and Laser Technology, 2024)
Graphene has arisen as an efficient photothermal (PT) nanomaterial owing to the strong light-matter interaction, ultrafast and nonradiative annihilation of the photoexcited carriers, and high thermal conductivity. Combined with the unique optical properties such as universal absorption coefficient at broadband wavelengths, the PT effect in graphene can be synergistically utilized for all-optical control of light. Here, we report an efficient transmission control of propagating light in graphene-covered side-polished fiber through the PT effect of graphene. When the local heat was generated via PT effect in graphene, a significant change in optical transmission was observed through two different mechanisms. The first one was implemented by the absorption change at the graphene layer via the asymmetrical reshaping of the mode-field distribution, resulting in the optical transmission change of up to 25 dB. The other mechanism was realized by the guiding property switching from the radiation mode to the guided mode of the light, resulting in the all-optical transmission control of over 56 dB at 1550 nm. The proposed method proves that the PT effect assists the broadband and efficient all-optical control with great versatility in graphene-integrated all-fiber devices.
Keywords: All optical; All-fiber devices; All-optical control; Efficient control; Optical control; Photothermal effects; Photothermal nanomaterials; Side-polished fiber; Transmission control; Wavelength independent operation; All-optical control; Graphene; Photothermal effect; Side-polished fiber; Wavelength-independent operation